Handwritten mathematical expression recognition : ScanIt a web based A\application - Sriram, Pranav (Nanyang Technological University, 2021)
With the increasing use of computational devices in our everyday lives, more and more tasks have transitioned to an easier methodology, using these devices. However, this is not the case for every single task. Some, like inputting mathematical expressions, have become even more tedious than they were to write out by hand. The goal of this project was to develop a web-based application that can help decrease the arduous nature of this task.